Understanding Greek warfare - Sears, Matthew A., author.
1 online resource.
Keywords: "This book offers the most comprehensive survey of Greek warfare, from the Mycenaeans through to the Hellenistic kingdoms' clashes with Rome. Each chapter provides an overview of the particular theme and historical period in question, and also a detailed discussion of the relevant sources. It covers not only the development of equipment, tactics, strategy, and the major wars of Greek history; it also treats the political, social, and cultural importance of warfare in each period. The major scholarly debates are outlined, and each chapter includes several short selections from the primary literary evidence. It is a crucial resource for anyone studying war in the ancient Greek world."--Provided by publisher.